Transferability of evidence-based parenting programs to routine implementation in postconflict South Sudan - Janowski, RK; Wessels, I; Bojo, S; Monday, F; Maloney, K; Achut, V; Oliver, D; Lachman, JM; Cluver, L; Ward, CL (SAGE Publications, 2020)
Purpose: This study investigated process and outcomes of the Parenting for Lifelong Health (PLH) for Young Children and for Adolescents programs implemented as part of routine service delivery in postconflict settings. Methods: These group-based programs were delivered by trained facilitators to 97 caregivers (PLH for Young Children) and 108 caregiver–adolescent dyads (PLH for Adolescents) over 12 or 14 (respectively) weekly sessions. Routine monitoring data were collected by the implementing partners using standardized self-report measures. Reducing harsh discipline was specified as the primary outcome, with secondary outcomes including improvements in positive parenting and reductions in poor parental supervision and parental inefficacy. Results: Analyses were intention to treat. Both PLH programs retained effectiveness in routine conditions in a postwar setting, with moderate to large effect sizes. The programs also had high enrollment and attendance rates, indicating high acceptability. Conclusions: Findings suggest promising viability for the implementation of evidence-based parenting programs in challenging postconflict contexts.